2009
DOI: 10.3928/00220124-20090824-02
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of New Nurses' Perceptions and Measured Performance-Based Clinical Competence

Abstract: This study provides a beginning understanding of the relationship between new nurses' perceptions and performance-based clinical competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 19 publications
5
49
1
Order By: Relevance
“…Therefore, these skills were regarded by students as advanced and difficult skills to perform. This finding is consistent with previous studies [26,27] .…”
Section: Discussion and Recommendationsupporting
confidence: 94%
“…Therefore, these skills were regarded by students as advanced and difficult skills to perform. This finding is consistent with previous studies [26,27] .…”
Section: Discussion and Recommendationsupporting
confidence: 94%
“…All the students correctly performed steps concerning preparation of equipment and tourniquet handling (1,6,8,13,25,32). All the students correctly assessed and selected a vein (7,27) in the category Assessment of a Vein. In the category Technical Implementation, four of the students traced the skin and all students inserted the cannula in a correct angle (26,29) while four students handled the cannula and stylet correctly (28,34).…”
Section: Correct Performancementioning
confidence: 99%
“…[5][6][7] Marshburn et al [7] claimed in their study that only 8% of newly qualified nurses were comfortable performing all the skills and procedures needed in a clinical setting. Starting an intravenous line was the skill nurses felt least comfortable in performing.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers have reported that new graduate nurses lack adequate levels of competence that are needed in the real world of clinical nursing practice to meet the ever-increasing demands in today's complicated healthcare environment [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the purpose of our study was to explore the difference in levels of clinical competence between students in the above-mentioned nursing programs and to identify skills that need to be reinforced in different nursing programs while the students are still attending school. The following research questions guided the study: (1) What are the levels of clinical competence reported by the nurse pregraduates? (2) What is the difference in levels of clinical competence between pregraduates attending different types of nursing programs?…”
Section: Introductionmentioning
confidence: 99%